Psychotropic Drugs and Outcome in Patients Receiving Anticoagulant Therapy for Venous Thromboembolism - Marchena, Pablo Javier; Tzoran, Inna; Brenner, Benjamin; Martín, Mar; Malý, Radovan; Bura-Riviere, Alessandra; Valle, Reina; Hernández-Blasco, Luis; López-Sáez, Juan Bosco; Monreal, Manuel; RIETE Investigators (Thrombosis and Haemostasis, 2020)
Background The influence (if any) of the use of psychotropic drugs on outcome in patients receiving anticoagulant therapy for venous thromboembolism (VTE) has not been consistently evaluated.Methods We used data from the RIETE (Registro Informatizado Enfermedad TromboEmbólica) database to compare the risk for VTE recurrences, major bleeding, or death during the course of anticoagulant therapy, according to the use of psychotropics at baseline.Results Among 49,007 patients with VTE enrolled from February 2009 to September 2019, total 5,230 (11%) were using psychotropics at baseline: antidepressants 3,273 (6.7%), antipsychotics 1,588 (3.2%), and anticholinesterases 369 (0.7%). During the course of anticoagulation, 1,259 patients developed VTE recurrences, 1,231 bled, and 3,988 died (fatal pulmonary embolism 269 and fatal bleeding 187). On multivariable analysis, patients using psychotropics at baseline had a similar risk for VTE recurrences (adjusted hazard ratio [HR]: 0.81; 95% confidence interval [CI]: 0.58–1.12), a nonsignificantly higher risk for major bleeding (adjusted HR: 1.15; 95% CI: 0.97–1.35), and a higher risk for intracranial bleeding (adjusted HR: 1.83; 95% CI: 1.32–2.53) or death (adjusted HR: 1.44; 95% CI: 1.32–1.57) compared with those not using psychotropics. When separately analyzed, the highest risk for intracranial bleeding was found in patients using antidepressants (adjusted HR: 1.60; 95% CI: 1.08–2.37) or antipsychotics (adjusted HR: 2.02; 95% CI: 1.17–3.49) but not in those on anticholinesterases (adjusted HR: 1.69; 95% CI: 0.62–4.60).Conclusion During the course anticoagulation for VTE, patients using psychotropics at baseline were at increased risk for intracranial bleeding.
Keywords: psychotropics; anticoagulant therapy; venous thromboembolism